Edukasi Perilaku Cuci Tangan Pakai Sabun (Ctps) Pada Siswa Kelas IV, V Dan VI Di SDN 026147 Tahun 2021 - Samuel M; Deli Syaputri; Dian Pratiwi; Risnawati Tanjung; Digna Renny (Jurnal Pengabdian Masyarakat Akademisi, 2022)
Washing hands with soap (CTPS) is a behavior that can support a clean and healthy life and avoid disease, one of which is diarrhea which is vulnerable to being experienced by children, especially school-age children. It is important to teach children from an early age about good and correct CTPS. This service is an activity that consists of education and demonstrations about hand washing with soap at SDN 026147 Binjai City. This activity aims to increase students' knowledge about the importance of washing hands with soap. The results of community service activities in the form of direct counseling experienced an increase in knowledge seen from the results of the pre-test by 27% and the results of the post-test by 93%. Community service activities in the form of counseling and direct demonstrations have increased skills seen from the pre-test results by 20% and post-test results occur by 93%